KOMUNIKASI POLITIK DI ERA DIGITAL - Nurul Hasfi (Program Magister Ilmu Politik, Universitas Diponegoro, 2019)
In the last two decades Internet has influenced aspects of human life including democracy. In Indonesian context, since the arrival of Internet in the last 1990s, it was creating new phenomenon known as online political communication. It dramatically have been changing the practice of traditional political communication mediated by convensional media. This article try to provide discussion theoretically and practically relating to the issue. Theoreticaly it explores of how internet has modified classical political communication theory; how new character of Internet has potential effect for producing better quality and quantity of political communication as well as how it has arised problematic issues on the process. Furthermore, this discussion briefly conclude that political communication in the future might never separate from this new medium. It may become most intriguing 'live laboratory' for researcher of the potential roles of the Internet in the political communication process.